Voltage imaging reveals the dynamic electrical signatures of human breast cancer cells - Peter Quicke; Yilin Sun; Mar Arias-Garcia; Melina Beykou; Corey D. Acker; Mustafa B. A. Djamgoz; Chris Bakal; Amanda J. Foust (Communications Biology, 2022)
Voltage imaging and machine learning reveal that human breast cancer cells exhibit voltage fluctuations absent in non-tumorigenic breast cells, beginning to shed light on the bioelectric properties of cancer processes.